Enlarging the ring by incorporating a phosphonate coligand: from the cyclic hexanuclear to octanuclear dysprosium clusters1. Issue 32 (28th August 2015) - Tian, Haiquan; Bao, Song-Song; Zheng, Li-Min
<x xml:space="preserve">Abstract</x> Two cyclic lanthanide clusters based on a rationally designed double pyrazinyl hydrazone ligand EDDC2−, namely, [Dy6(EDDC)2(OAc)14(H2O)2]·MeOH·2H2O (1) and [Dy8(EDDC)4(O3PC10H7)4(OAc)8(H2O)4]·12H2O (2) are reported. The latter shows slow magnetization relaxation below 12 K.